Chemotherapy For Elderly Patients With Gastric Cancer: Experience Of A Brazilian Center - Pedro Aguiar Jr.; Gustavo Stock; Katia Barão; Nora Forones (Geriatrics, Gerontology and Aging)
OBJECTIVE: Gastric cancer (GC) is one of the most common cancers, and its incidence increases with age. The objective of the study was to evaluate the response rate (RR), overall survival (OS), and toxicity in patients aged over 60 years, with metastatic GC and who were undergoing chemotherapy. METHODS: This is a retrospective study developed in a university hospital. Medical records of patients treated in the last 4 years were analyzed. RESULTS: Twenty-one patients were included; the average age was 69.6 ± 7.6 years, 76.2% men, 61.9% Karnofsky Performance Status (KPS) ≥ 70, 85.7% had weight loss > 10% in 6 months, 28.6% had at least 2 sites of metastasis, and 42.9% had unfavorable histology (diffuse). Most of the patients (85.7%) were treated with combination regimens (4.6 cycles on average). Patients with better nutritional status had a non-statistically significant better tolerance to the treatment (p = 0.17). The median progression-free survival (PFS) was 9.0 months and the median OS was 13.8 months. Toxicity grade 1–2 was observed in 61.9%, and grade 3–4, in 14.3%. Less than two sites of metastasis (hazard ratio [HR] = 0.15; CI95% 0.02 – 0.93), absence of metastasis to non-regional lymph nodes (HR = 0.04; CI95% > 0.01 – 0.44), higher number of chemotherapy cycles (HR = 0.72; CI95% 0.53 – 0.97), objective response (HR = 0.06; CI95% 0.01 – 0.69) were associated with higher OS. Higher body mass index (BMI) was related with a not statistically significant better OS (HR = 0.84; CI95% 0.64 – 1.10). CONCLUSIONS: Patients treated in our hospital showed results compatible with literature. The doublet chemotherapy is feasible in elderly individuals with manageable toxicity.